PENDIDIKAN ISLAM DI SUDAN - Murjani Murjani (CV. ADIBA AISHA AMIRA, 2022)
The entry of Islam in Africa‎ began at the time of the Prophet Muhammad when there was the first contact between Islam and Africa‎, namely after the friends moved to Habsyi and received a good reception from the king of Najjasyi and the local population. The spread of Islam was then continued during the Caliph Umar Ibn Khattab by sending Amr ibn 'Ash. The development of Islam has been stronger since Sudan was under the Ottoman Turks starting in the 16th century and under Egyptian rule since 1822. Almost all citizens of northern Sudan adhere to Islam, while the southern part of Sudan until now the majority of the population is Christian and some (17%) remain. as a follower of the teachings of watsani (animist).